Biocomposite Active Whey Protein Films with Thyme Reinforced by Electrospun Polylactic Acid Fiber Mat - Andreea (Lanciu) Dorofte; Iulia Bleoanca; Florentina Ionela Bucur; Gabriel Mustatea; Daniela Borda; Felicia Stan; Catalin Fetecau (Foods)
Electrospinning is a versatile technique for obtaining nano/micro fibers which are able to significantly change the active properties of composite materials and bring in new dimensions to agri-food applications. Composite bio-based packaging materials obtained from whey proteins, functionalized with thyme essential oil (TEO) and reinforced by electrospun polylactic acid (PLA) fibers, represent a promising solution for developing new active food packaging using environmentally friendly materials. The aim of this study is to obtain and characterize one-side-active composite films covered with a PLA fiber mat: (i) WF/G1, WF/G2, and WF/G3 resulting from electrospinning with one needle at different electrospinning times of 90, 150, and 210 min, respectively, and (ii) WF/G4 obtained with two face-to-face needles after 210 min of electrospinning. While TEO bioactivity is mainly related to its antimicrobial and antioxidant properties, the PLA fiber mat uplifted the composite mechanical and barrier properties of films. The bi-layer films obtained were characterized by SEM, showing the distribution of the electrospun fiber mat and an increased thickness of the PLA layer from WF/G1 to WF/G4, while FTIR spectra showed the structural vibrations of the functional groups. The experimental results show that WF/G4 have a FTIR fingerprint resembling PLA, retained ~50% of the volatile compounds present in the uncovered film (WF/TEO), while it only had 1.41 ± 0.14 (%) of the permeability to octanol of the WF/G1 film. WF/G4 exhibited 33.73% of the WVP of WF/G1 and displayed the highest tensile strength, about 2.70 times higher than WF/TEO. All films studied revealed similar antimicrobial effect against Bacillus cereus, Geotrichum candidum, and Rhodotorula glutinis and good antiradical activity, thus demonstrating good prospects to be applied as food packaging materials. WF/G composite materials are good candidates to be used as bioactive flavoring primary packaging in hard cheese making.